Correlation of fatty acid composition of virgin olive oil with thermal and physical properties. Issue 3 (10th September 2014) - Gila, Abraham; Jiménez, Antonio; Beltrán, Gabriel; Romero, Alberto
<x xml:space="preserve">Abstract</x> Physical properties (dynamic viscosity and density) of virgin olive oil (VOO) from fourteen olive varieties were studied as a function of their fatty acid (FA) compositions and temperature. Moreover, for these same VOOs, were evaluated the thermal properties by Differential Scanning Calorimetry (DSC): cooling, heating, and oxidation profiles. The composition of VOO analyzed corresponded to the normal range for these varieties. Also, for all VOOs, the temperature effect on oil density decreased linearly as a temperature increased, achieved a good correlation. Arrhenius model describes the effect of temperature on viscosity showing a Newtonian behavior. Correlations between temperature of the major peak of crystallization phase (Pc) and their content in oleic and linoleic FAs were found. In addition, although a not very good correlation was observed between FA composition and viscosity, it was observed that the viscosity tends to increase with the amount of oleic acid. Practical applications: Knowledge of thermal and physical properties of the virgin olive oils (VOOs) is essential to improve some aspects of the extraction process in olive oil mill. Therefore, the information in this work is important for many applications such as equipment design (settling and storage tanks, centrifuges, pumps, etc.). <inline-graphic xlink:href="ark:/27927/pgj983cnth" content-type="ejlt201400078-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Correlations between the oleic acid (C18:1) content of VOOs and the corresponding to (A) temperature of the major peak of crystallization phase (Pc) and (B) dynamic viscosities (µ). The aim of this work is to study not only thermal properties from thermal profiles (crystallization, melting, and oxidation curves) by DSC measurements, but also physical characterization (density and viscosity) as a function of temperature of VOOs from 14 different olive cultivars, in order to relate thermal and physical properties with chemical composition (FA). As can observed, there is a high correlation between temperature of the peak of crystallization phase, Pc, and FAs composition (C18:1). Moreover, although non good correlations between oil viscosity and fatty acid composition could be found, the viscosity tends to increase as the amount of C18:1 fatty acid.